136k views
4 votes
Write the quadratic equation in factored form
x^2 + x - 12 = 0

User Zrvan
by
5.5k points

2 Answers

4 votes

Answer:(x + 4)(x - 3) = 0


Step-by-step explanation: See here we have to write the given equation in quadratic form.

The equation given here is,

x^2 + x - 12 = 0

i.e. x ^ 2 + 4x - 3x - 12 = 0

i.e. x(x + 4) - 3(x + 4) = 0

Therefore its factored form will be

(x + 4)(x - 3) = 0

Hope it helps!!!


User Eddy Ed
by
6.1k points
5 votes

For this case we must factor the equation of the second degree of the form
ax ^ 2 + bx + c = 0

To factor, we must find two numbers that when multiplied result in -12, and when summed give as result +1.

Those numbers are +4 and -3.

Taking into account that
+ * - = - and that different signs are subtracted and the sign of the major is placed.


(4) * (- 3) = - 12\\+ 4-3 = + 1

Thus, the factored expression is:


(x + 4) (x-3) = 0

Answer:


(x + 4) (x-3) = 0


User Xristina
by
4.4k points